2015
DOI: 10.1111/cns.12438
|View full text |Cite
|
Sign up to set email alerts
|

L‐3‐n‐butylphthalide Promotes Neurogenesis and Neuroplasticity in Cerebral Ischemic Rats

Abstract: It first demonstrates that l-NBP may improve the behavioral outcome of cerebral ischemia by promoting neurogenesis and neuroplasticity. Activation of CREB and Akt and inhibition of STAT3 signaling might be involved in.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 33 publications
(33 reference statements)
4
58
0
Order By: Relevance
“…It has been hypothesized that there is a possibility of migration of newborn precursor cells to the damage areas prior to maturation. However, the downfall is that newly generated cells hardly survive [29]. A recent study stated that dl-NBP stimulates the angiogenic process and protects the brain microvascular endothelial cells (BMECs) against oxygen glucose deprivation (OGD), by means of an increase of HIF-1 α and Bcl-2 expressions [24].…”
Section: Nbp and Ischemic Strokementioning
confidence: 99%
See 2 more Smart Citations
“…It has been hypothesized that there is a possibility of migration of newborn precursor cells to the damage areas prior to maturation. However, the downfall is that newly generated cells hardly survive [29]. A recent study stated that dl-NBP stimulates the angiogenic process and protects the brain microvascular endothelial cells (BMECs) against oxygen glucose deprivation (OGD), by means of an increase of HIF-1 α and Bcl-2 expressions [24].…”
Section: Nbp and Ischemic Strokementioning
confidence: 99%
“…A recent study stated that dl-NBP stimulates the angiogenic process and protects the brain microvascular endothelial cells (BMECs) against oxygen glucose deprivation (OGD), by means of an increase of HIF-1 α and Bcl-2 expressions [24]. Additionally, studies on newborn neural cells showed that l-NBP improves their proliferation, survival, and differentiation [29]. The underlying process has been described as through an increase of 5-bromo-2′-deoxyuridine- (BRdU-) positive cells in the dentate gyrus of damaged areas.…”
Section: Nbp and Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…N -butylphthalide (NBP), a new drug extracted from celery seeds (see Figure 1 ), was approved by China Food and Drug Administration in 2002. To date, many experiments confirm that NBP treatment could significantly reduce oxidative damage, regulate energy metabolism, and alleviate cerebral edema in acute focal cerebral ischemia rats, protecting mitochondria function from brain damage directly through BBB in patients with acute and chronic cerebral ischemia and dementia (Yang et al, 2015). Meanwhile, NBP had also positive effects in stabilizing the NVUs and improving the neurological deficits through its primary target vascular endothelium (Li et al, 2007; Thored et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment mechanisms of butylphthalide include mobilization of circulating endothelial progenitor cells [12] and promoting neurogenesis and neuroplasticity in the brain. [13] In addition, previous study has shown that butylphthalide has a neuroprotective effect in rats after acute CO poisoning. [14] We speculated that a combined therapy of MSC transplantation and butylphthalide might have a promising treatment outcome for DEACMP.…”
Section: Introductionmentioning
confidence: 99%